Kesenjangan Pembangunan di Tingkat Lokal: Refleksi atas Implementasi Otonomi Daerah di Indonesia - Fathur Rahman; Arifah Astagini; Ahmad Dellan Fahmi Effendy (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2020)
ABSTRACT Development a process that is carried out continuously in order to improve social and economic indicators in a region over time. Blitar Regency is one of regions that has made efforts to improve development. However, in reality there are still areas in Blitar which have development gap, the development only focuses on North Blitar compared to South Blitar. This makes researcher interested in going over the Development Gap in Blitar District as a study. This study aims to determine the causes of the development gap in northern and southern Blitar Districts, in education and health from 1999-2014 by using case study of Kanigoro and Bakung Districts. In this study, direct interviews were conducted with all actors involved with several indicators from education and health sectors which were analyzed using qualitative method. The results of the analysis are presented through interviews which indicate that the causes of development gap in northern and southern Blitar in the education sector are the construction of supporting facilities more focused in Kanigoro District as the downtown, while in Bakung District is only for building maintenance. So, that the school supporting facilities in the Kanigoro District are more complete compared to the Bakung District. Furthermore, development gap also occurs in the health sector, the health center facilities in Kanigoro District does not yet have hospitalization, while in Bakung District has 6 beds for hospitalization. However, Kanigoro District still has a more complete quality of health because in the Kanigoro District there is a Medika Husada Hospital and close to the Ngudi Waluyo general hospital in Wlingi District.